As contribuições da escola no processo do indivíduo preto em tornar-se negro - Rosa, Alline Caruzo (2023)
This research falls within the research line of the “School Institution: organization, pedagogical practices, and educator training”, and its object of study is the trajectory of Black adults who experienced their schooling process in the municipality of Ribeirão Pires. Its main question is: How did the school influence the process of identity recognition of Black individuals? Therefore, the general objective is to understand how the school experiences of Black individuals, currently aged between 30 and 35, influenced their trajectories concerning "becoming Black." The specific objectives are as follows: 1- Identify common practices in the daily school life that express or do not express cultural diversity and the appreciation of Afro-descendant topics; 2- Analyze, based on the trajectory of Black individuals, situations and educational experiences that influenced the construction of positive or negative representations of Blackness; 3- Recognize events and situations that contribute to the perception of Black individuals in the act of "becoming Black." The theoretical framework that underpins this study consists of Black authors such as Cavalleiro, Gomes, Gonzales, and Santos. From a methodological point of view, this research was carried out through two interviews, based on the six moments proposed by Lahire in the work "sociological portraits": describing the disposition, genesis of the disposition, series of coherent behaviors, attitudes and practices, relatively similar experiences, transferability of contexts, and inhibition